The Study of Students’ Basic Literacy and Mental Health Training Strategies Based on Ideological and Physical Education - Chen Xie; Yanqi Nong; Wanying Fu; Dongxia Pan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Cultural education, as the key course content to build students' literacy and thought, is at the forefront of ideology. The adverse influence of news media on students' ideas, opinions and consciousness will weaken the discourse power of moral education. This article takes the media era as the breakthrough point, based on the moral education as the core idea, with the rapid development of students 'core literacy as the main line, to students' core literacy as the main body of scientific research, discusses the interaction between moral education and students' core literacy and logical sequence, organize cultural education, core idea, management system, the main content, way, evaluation way. Social morality and physical and mental health are also hot topics in the university education industry. With the deep level of research and discussion in recent years, the rapid development of this research has entered a systematic link. The new ideas and achievements produced by the ideological analysis and systematization of college students' mental health are the quality and prerequisite of higher vocational education. According to this reason and teaching environment, the paper discusses the implementation path and construction preventive measures of college students from the perspective of ideological and Physical courses.